HUBUNGAN KEHAMILAN TIDAK DIINGINKAN DENGAN KEJADIAN STUNTING PADA ANAK USIA 0-5 TAHUN DI INDONESIA (ANALISIS DATA RISKESDAS 2013) - Annisa Lidra Maribeth; Naima Lassie; Yuni Handayani Gusmira (Yayasan Nusantara Hasana Berdikari, 2022)
Indonesia has become 5th top country with biggest stunting rate in the world. Unintended pregnancies can be one of the factors that may play a major role in causing the incidence of stunting in children aged 0-5 years. This study aims to analyze the relationship of unintended pregnancies with incidence of stunting in children aged 0-5 years. This quantitative research used secondary data from National Health Research (Riskesdas) with cross sectional research methods. This research covered all provinces and districts / cities in Indonesia which were carried out from preparation to further analysis in January 2012 - December 2014 and the secondary data was processed in 2019. The sample of this study was women aged 15-49 years old with children 0-5 years old in Indonesia which amount to 42,684 people. Results: In bivariate analysis using chi-square test, it was found that the relationship of unintended pregnancies with stunting have a p value of 0.04 (OR: 1.059 and 95% CI: 1.003-1.118). In multivariate test using logistic regression tests, the relationship of unintended pregnancies became insignificant to stunting with p-value 0, 077 (OR: 1.051; 95% CI: 0.995-1,110). There are two confounding variabels, economic status and education related significantly to stunting with p value <0.001. Conclusion: in multivariate analysis there was no relathionship of unintended pregnancy with stunting in children under five years old ( p value> 0.05). There is confounding in this study, the educational variable and economic status are confounding variable. Education and economic status have a significant relationship on multivariate analysis (p value< 0.001) with stunting.